2017
DOI: 10.1002/mc.22742
|View full text |Cite
|
Sign up to set email alerts
|

ITIH5 induces a shift in TGF‐β superfamily signaling involving Endoglin and reduces risk for breast cancer metastasis and tumor death

Abstract: ITIH5 has been proposed being a novel tumor suppressor in various tumor entities including breast cancer. Recently, ITIH5 was furthermore identified as metastasis suppressor gene in pancreatic carcinoma. In this study we aimed to specify the impact of ITIH5 on metastasis in breast cancer. Therefore, DNA methylation of ITIH5 promoter regions was assessed in breast cancer metastases using the TCGA portal and methylation-specific PCR (MSP). We reveal that the ITIH5 upstream promoter region is particularly respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 65 publications
(183 reference statements)
4
26
0
Order By: Relevance
“…In 2008, ITIH5 was described to be epigenetically silenced in breast cancer [17] and five years later ITIH5 DNA methylation has been identified as a putative blood-based biomarker for the early detection of breast cancer [38]. Since then functionally studies revealed, for instance, ITIH5 mediated suppression of breast [21,22] and pancreatic cancer metastases [23] in vitro and in vivo. Interestingly, in aggressive mammary cancer cells, ITIH5 triggered an epigenetic reprogramming which was associated with a demethylation of various promoter regions, including that of DAPK1, a tumor suppressor gene and putative blood-based biomarker in several tumor entities [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, ITIH5 was described to be epigenetically silenced in breast cancer [17] and five years later ITIH5 DNA methylation has been identified as a putative blood-based biomarker for the early detection of breast cancer [38]. Since then functionally studies revealed, for instance, ITIH5 mediated suppression of breast [21,22] and pancreatic cancer metastases [23] in vitro and in vivo. Interestingly, in aggressive mammary cancer cells, ITIH5 triggered an epigenetic reprogramming which was associated with a demethylation of various promoter regions, including that of DAPK1, a tumor suppressor gene and putative blood-based biomarker in several tumor entities [21].…”
Section: Discussionmentioning
confidence: 99%
“…ITIH5 has previously been shown to be epigenetically silenced in various cancer entities [17][18][19], including bladder cancer [20], where its expression was associated with tumor recurrence of the clinical important group of high-grade pT1 patients. In addition, ITIH5 was characterized as a putative metastasis suppressor gene in breast [21,22] and pancreatic cancers [23]. ECRG4 has also been described to be a candidate tumor suppressor gene that is inactivated by DNA methylation in cancers, like esophageal squamous cell carcinoma [24,25], breast cancer [26], renal cell cancer [27], and colorectal cancer [28,29], but not in bladder cancer so far.…”
Section: Introductionmentioning
confidence: 99%
“…25 Specifically, the HC5 gene has been identified as a tumor suppressor gene in multiple types of cancer, including breast, bladder, pancreatic, and colon cancer and acute myeloid leukemia. 206210 It can suppress the proliferation and migration of breast, bladder, and colon cancer cells in vitro. 206,207,210 HC5 gene expression is reduced in cancer due to the aberrant hypermethylation of the promoter.…”
Section: Roles Of Iαi In Pathologymentioning
confidence: 99%
“…206210 It can suppress the proliferation and migration of breast, bladder, and colon cancer cells in vitro. 206,207,210 HC5 gene expression is reduced in cancer due to the aberrant hypermethylation of the promoter. 208,211 Expression of the HC5 gene predicts longer overall survival in gastric and breast cancer and lung adenocarcinoma.…”
Section: Roles Of Iαi In Pathologymentioning
confidence: 99%
See 1 more Smart Citation